2009
DOI: 10.1007/s10571-009-9421-3
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Effects of Ginsenosides on Calcineurin Activity and Tau Phosphorylation in SY5Y Cells

Abstract: Calcineurin (CN) is a Ca(2+)/calmodulin-dependent protein phosphatase expressed at high levels in brain. Many findings have shown that calcineurin plays an important role in tau hyperphosphorylation, which is one of the neuropathologic features in the brains of Alzheimer's disease (AD). Based on the molecular screening model using p-nitrophenyl phosphate (p-NPP) as a substrate for preliminary screening and (32)P-labeled 19-residue phosphopeptide as a specific substrate for final determination, we found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Ginseng extract or ginsenosides have been shown to protect astroor ginsenosides have been shown to protect astrohave been shown to protect astrocytes grown in primary culture [12,13]. In other studies, ginseng total saponin protected human neuroblastoma cells from cyclosporine A-induced calcineurin inhibifrom cyclosporine A-induced calcineurin inhibifrom cyclosporine A-induced calcineurin inhibition and tau hyperphosphorylation [14], and improved depression caused by forced swim and chronic stress [15]. Ginsenoside Rb1 was shown to repress cell death induced by 6-hydroxydopamine in SH-SY5Y neuroblastoma cells [16], and protected dopaminergic cells from oxidative stress [17,18].…”
Section: Anti-apoptotic Effects Of Red Ginseng On Oxidative Stress Inmentioning
confidence: 96%
“…Ginseng extract or ginsenosides have been shown to protect astroor ginsenosides have been shown to protect astrohave been shown to protect astrocytes grown in primary culture [12,13]. In other studies, ginseng total saponin protected human neuroblastoma cells from cyclosporine A-induced calcineurin inhibifrom cyclosporine A-induced calcineurin inhibifrom cyclosporine A-induced calcineurin inhibition and tau hyperphosphorylation [14], and improved depression caused by forced swim and chronic stress [15]. Ginsenoside Rb1 was shown to repress cell death induced by 6-hydroxydopamine in SH-SY5Y neuroblastoma cells [16], and protected dopaminergic cells from oxidative stress [17,18].…”
Section: Anti-apoptotic Effects Of Red Ginseng On Oxidative Stress Inmentioning
confidence: 96%
“…Previously, we have established a standard protocol for CN's activity assay in SH-SY5Y cells (26). 293T cells are abundant of CN and easy to perform transfection according to our research (27).…”
Section: Traf3 Inhibits Cn's Activitymentioning
confidence: 99%
“…Currently, many in vivo and in vitro studies have shown its beneficial effects in aging, central nervous system (CNS) disorders, and neurodegenerative diseases, such as AD [3,4]. Ginsenosides Rg1 (GRg1) and Rb1 (GRb1) as the main pharmacologically active ingredients of ginseng have been proved in their effectiveness in AD prevention and treatment [5,6]. In addition, previous studies have demonstrated that they exert its effects on multiple sites of action like Regulation of neurite outgrowth [7], inhibition of Neuroinflammation [8], reducing the level of Aβ [9] and so on.…”
Section: Introductionmentioning
confidence: 99%